Preparation and Characterization of Porous Natural Rubber Loaded with Silver Nanoparticles - Thanasuwannakul, Nut; Buntum, Tanawat; Suwantong*, Orawan (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
In this study, porous natural rubber (NR) films loaded with silver nanoparticles (AgNPs) were prepared by the solvent casting method. The porous structure of the NR films was formed with hydrophilic substances such as glycerol, pectin or carrageenan. The film properties including morphology, mechanical test, hydrophilicity evaluation, water absorption, release study, and antibacterial activity were determined. From the results, the morphology of films was a continuous porous structure on the surface of films. The pectin and carrageenan enhanced porosity, hydrophilicity, and water sorption of the porous NR films. The developed porous NR films could sustain the release of Ag+ ions for 2 days and showed inhibition zones against Staphylococcus aureus and Escherichia coli. Therefore, these porous NR films have the potential to be used as chronic wound dressing. Keywords: natural rubber; porous film; silver nanoparticle; pectin; carrageenan *Corresponding author: Tel.: (+66) 53916787 Fax: (+66) 53916776 E-mail: o.suwantong@gmail.com